The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1992
DOI: 10.1017/s0016672300030640
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and structure of cloned P elements from theDrosophila melanogasterP strain π2

Abstract: P transposable elements of Drosophila melanogaster cloned from the strong P strain ?7 2 have been analysed. The structures and chromosomal locations of 26 of the 30-50 elements estimated to be present in n 2 have been determined. At one location two elements are inserted 100 base pairs (bp) apart, and in a second location two elements are only separated by the 8 bp duplicated upon P-element insertion. In addition to 2-9 kilobasepair (kbp) elements, elements with 14 different internal deletions from 1-3 to 2-3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
47
0

Year Published

1994
1994
2008
2008

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(56 citation statements)
references
References 35 publications
9
47
0
Order By: Relevance
“…the case of a strong P strain r2, in which the numbers of P elements are approximately 30-SO, seven out of 26 P elements were complete P elements (O'Hare & Rubin, 1983;O'Hare et al, 1992). The ratio of complete P elements to total P elements is lower in NP280 and WY1 13.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…the case of a strong P strain r2, in which the numbers of P elements are approximately 30-SO, seven out of 26 P elements were complete P elements (O'Hare & Rubin, 1983;O'Hare et al, 1992). The ratio of complete P elements to total P elements is lower in NP280 and WY1 13.…”
Section: Discussionmentioning
confidence: 92%
“…The number of complete P elements in a reference P strain, jr2, was estimated as one-third of the total number of P elements. Sequences of P elements from Drosophila melanogaster from diverse geographical locations are homogeneous and very similar to those of Drosophila willistoni (O'Hare & Rubin, 1983;Iwano et a!., 1984;Sakoyama etal., 1985;Black etal., 1987;Daniels eta!., 1990;O'Hare et al, 1992). Moreover, the distribution of P elements is restricted in Drosophila ,neianogaster, and other closely related species have no P element sequence (Brookfield et al, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…Gloor, personal communication). The analysis of the P element complement of a natural P strain (7r2) has also suggested that the complete P element could play a role in the P cytotype determination of this strain, since determinants of P cytotype have been genetically located on all maj or chromosomes and the complete P element is the only type of element also present on all chromosomes (O'Hare et al, 1992). P elements derived from natural chromosomes have also been genetically isolated.…”
Section: Type Of Repressor Making P Elementsmentioning
confidence: 99%
“…P strains exhibit low to high levels of P activity potential and low levels of P susceptibility, while Q strains show extremely low levels of both P activity and P susceptibility. Both types have been shown to possess 30-50 copies of P elements per genome, of which about a third are the 2.9 kb elements and the rest are deleted derivatives (Bingham et al, 1982;Black et al, 1987;O'Hare et al, 1992). M and M 0 strains do not exhibit any significant level of P activity.…”
Section: Introductionmentioning
confidence: 99%